2020
DOI: 10.1111/tesg.12457
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Play Policies: Disabled Children And Their Access To Dutch Playgrounds

Abstract: Despite the 1989 UN Convention on the Rights of the Child, many cities are still struggling to facilitate inclusive playgrounds. This paper contributes to our understanding of the everyday landscapes of disabled childhood, by investigating the play‐policy of Dutch municipalities via a mixed‐methods approach. Our online survey reveals that 90 per cent have a play‐policy, although the length and content of these documents vary extensively, and accessibility and inclusive play are often lacking. Additionally, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 31 publications
0
21
0
1
Order By: Relevance
“…Children with disabilities and parents of children with disabilities both voiced a desire for playgrounds that offer adapted equipment often not found at conventional playgrounds that meets their child's needs, abilities and interests (10,47). However, studies have found a lack of specialized equipment (e.g., wheelchair accessible swings) for children with disabilities across playgrounds (12,13,15,22,24,26,39,40,52,53). Traditional types of playground equipment (e.g., slides, swings) are generally inaccessible to some children with disabilities without caregiver assistance (14), and the work of physically transferring a child becomes increasingly difficulty as children grow older and heavier (10,16).…”
Section: Play Equipment Accessible To All Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…Children with disabilities and parents of children with disabilities both voiced a desire for playgrounds that offer adapted equipment often not found at conventional playgrounds that meets their child's needs, abilities and interests (10,47). However, studies have found a lack of specialized equipment (e.g., wheelchair accessible swings) for children with disabilities across playgrounds (12,13,15,22,24,26,39,40,52,53). Traditional types of playground equipment (e.g., slides, swings) are generally inaccessible to some children with disabilities without caregiver assistance (14), and the work of physically transferring a child becomes increasingly difficulty as children grow older and heavier (10,16).…”
Section: Play Equipment Accessible To All Childrenmentioning
confidence: 99%
“…This playground element refers to the stages involved in determining how a playground should be designed with a focus on meeting the needs of children with disabilities. Including playground users in the design process was a key recommendation that emerged for this playground element [7 out of 35 studies; (13,14,21,46,47,52,55)]. Despite research indicating that municipal playground personnel and the construction industry have inadequate knowledge regarding the needs of children with disabilities (14,52), there has been a lack of representation from individuals with lived experience (e.g., children with disabilities and their caregivers) or those who work closely with children with disabilities (e.g., disability organizations, occupational therapists) when designing playgrounds (13,14,52).…”
Section: Design Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Incluir as crianças na cidade, ouvindo-as sobre os espaços em que vivem, deverá constituir uma prioridade nos vários campos da sociedade nos tempos vindouros. Envolver as crianças no planeamento urbano, incluindo os grupos mais vulneráveis, passa pelo estabelecimento de um processo aberto de comunicação com os municípios (Melik & Althuizen, 2020). Muito há ainda a fazer para ouvirmos as crianças e lhes darmos o espaço e protagonismo que sempre deveriam ter sido seus.…”
Section: As Crianças E Os Seus Usos Dos Espaços Públicosunclassified
“…For youth with and without a disability, the physical environment can act as a facilitator or barrier towards becoming physically active 12,62 . For example, playgrounds in the Netherlands are often not inclusive for youth with a disability, limiting their opportunity to be physically active around their home 63 . Through increased wheelchair mobility, some obstacle in the physical environment, e.g.…”
Section: Physical Environment and Wheelchair Mobilitymentioning
confidence: 99%